Gas-cooled reactors today. Volume 2, proceedings of the conference held in Bristol on 20-24 September 1982. (British Nuclear Energy Society, 1982)
Papers are organised by the following session titles: 'Magnox Experience and Nuclear Fuel Testing', 'AGR Fuel', 'Graphite Corrosion and Coolant Chemistry', 'HTR and GCFR Fuel', 'Structural Materials in Helium-cooled Reactors' and 'Structural Materials for Magnox and AGRs'.